A Randomly Selected Chamber: Promises and Challenges - Antoine Verret-Hamelin; Pierre-Etienne Vandamme (Journal of Deliberative Democracy)
This paper explores the idea of a randomly selected chamber of representatives (RSC) through an appreciation of the promises it offers and the challenges it would face. We identify two main promises: a RSC could offset the aristocratic character of elections, thereby increasing the legitimacy of the political system; and it could increase democracy’s epistemic potential, thanks to gains in terms of diversity, deliberations, humility, and long-term perspective. We then discuss four key challenges. First, participation: how can the chamber have diversity without mandatory participation or heavy sanctions? Second, how can we conceive or build legitimacy for this non-elected and somehow unaccountable chamber’s views? Third, independence: how to safeguard randomly selected people from corruption? Finally, there may be a linguistic challenge: if the RSC has a deliberative role, how should it cope with the possible linguistic diversity of its members? We conclude that these challenges are not insurmountable, but reveal some trade-offs that cannot be entirely dissolved.